School Climate and Organisational Commitment among Secondary School Teachers for Sustainable Development in Oyo State, Nigeria - Oredein, Afolakemi Olasumbo; Bello, Elizabeth O. (Advances in Social Sciences Research Journal, 2022)
This study investigated the relationship between school climate and organisational commitment among public secondary schools in Oyo State, Nigeria. A descriptive research design survey type was adopted in this study. Two research questions were posed and one hypothesis was formulated for the study. The population consisted of 604 principals and 14,508 teachers from secondary schools in Oyo State, Nigeria. The Multistage sampling procedure uses the Simple Random Sampling technique to select 2,960 teachers. One structured questionnaire, (SCOCQ) was validated as having a Cronbach’s Alpha reliability value of 0.87. The descriptive statistics of mean and percentages were used to analyse the demographic variables and research questions while Pearson Product Moment Correlation was used for the hypothesis. The result revealed the status of organisational commitment and school climate is moderate (weighted mean = 2.82 and 2.80), and Affective is the highest (X= 3.35), Also, the study revealed that there is a significant relationship between school climate and organizational commitment to education sustainable development in Nigeria. Based on the findings, the study concludes that school climate influences teachers’ organisational commitment. However, based on the findings, recommendations were made to improve and make the school climate conducive to teaching-learning.